Oral Hairy Leukoplakia in Patient with HIV/AIDS - Agustina Tri Pujiastuti; Dwi Murtiastutik (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Oral hairy leukoplakia (OHL) is an asymptomatic white plaque with vertical corrugations most commonly found on the lateral borders of the tongue. It is caused by local infection of Epstein- Barr Virus (EBV). OHL is usually associated with immunocompromised condition, and mainly described in patients with human immunodeficiency virus (HIV). Purpose: to report a case of oral hairy leukoplakia in an HIV patient that is often misdiagnosed as oral candidasis. Case: A 44-years old female came to the Dermato-Venereology Outpatient Clinic of Dr. Soetomo General Hospital Surabaya with complaint of persistent asymptomatic whitish color on both borders of her tongue. History taking revealed that at first the whitish color appeared spreading on the tongue, but after taking antifungal treatment, only the lesion on the borders still persisted, all attempts to scrub off the lesion failed. There were also history of diarrhea, fever and cough for almost 1 month. Further examination of HIV antibody 3 method tests revealed reactive result with CD4+ count of 1 cel/uL. Physical examination revealed bilateral painless white well demarcated plaque with “hairy” like corrugated appearance on the lateral borders of the tongue. Discussion: From history, clinical findings, and the reactive HIV antibody examination, the patient was diagnosed with AIDS with oral hairy leukoplakia. The patient was treated with acyclovir 200 mg, 5 times daily. After 2 weeks of treatment, clearance was achieved. Conclusion: The establishment of OHL which oftenly mistaken as oral candidiasis has a diagnostic value for HIV infection. Systemic antiviral institution and antiretroviral (ARV) medications as prevention for recurrence gave satisfying result. Key words: oral hairy leukoplakia, HIV, acyclovir.